Penerapan Model Bimbingan Klasikal Sciarra pada Kompetensi Memperoleh Pengetahuan untuk Mencapai Tujuan Karir Siswa Kelas X di Sekolah Menengah Atas Negeri 1 Indralaya - Erni, Erni; Yosef, Yosef; Harlina, Harlina (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2017)
This study aims to determine the application of classical models Sciarra guidance on competence gained knowledge to achieve career goals of students and to determine the effectiveness of the application of classical models Sciarra guidance on competence gained knowledge to achieve career goals of students. Subjects were students of class X Senior High School No. 1 Indralaya with a sample of 33 students of class X Natural Science 4 randomly selected. The study design used is one group pretest posttest design. The results showed differences in pretest and posttest results were higher after the students followed the classical model of counseling services Sciarra. From the results of hypothesis testing can be concluded that the model of classical Sciarra guidance effectively applied as a classical method of service delivery.